Foodgrain market integration under market reforms in Egypt - Goletti, Francesco; Badiane, Ousmane; Sil, Jayashree (International Food Policy Research Institute, 1994)
Using urban price data for the period 1976 to 1992 and rural price data for the period 1982 to 1992, the study assesses the degree of market integration for wheat, maize and rice. The study finds that i) reforms have not destabilized foodgrain prices; ii) there is some indication that the degree of segmentation among food grain markets has decreased during the reform period, especially for rural wheat and maize markets; iii) urban markets exhibit a much higher degree of market segmentation, particularly for wheat; and iv) the extent of market integration in terms of the magnitude of market interdependence and speed of price transmission was until 1992 very limited. Urban markets seemed to have a lower magnitude of integration than those of rural areas and the speed of adjustment was higher among these markets, reflecting the better communication and infrastructure network in urban areas.